Animal performance and environmental efficiency of cool- and warm-season annual grazing systems. (16th March 2018) - Leanne Dillard, S; Hancock, Dennis W; Harmon, Deidre D; Kimberly Mullenix, M; Beck, Paul A; Soder, Kathy J
Abstract: Annual forage crops can provide short-term grazing between crop rotations or can be interseeded into perennial pastures to increase forage quality and productivity. They also provide an opportunity to increase the economic and environmental sustainability of grazing systems. Cool-season annual forage crops provide high-quality, abundant forage biomass when forage availability from perennial forage species is lacking, reducing the need for stored feeds during the winter months. For example, ADG of 1.5 kg have been reported using small grains alone and in mixtures with annual ryegrass ( Lolium multiflorum Lam.) while maintaining an average stocking rate of 3.5 animals/ha. No-till (NT) establishment has been shown to be as effective as conventional tillage for establishing small grain pastures. Stocker performance during the fall was not affected by tillage treatment, but during the spring grazeout, BW gain per hectare was 8% greater in NT pastures. An in vitro study showed that daily production of CH4 was 84% lower, respectively, in turnip ( Brassica rapa L.) and rapeseed ( B. napus L.) diets compared with annual ryegrass. Warm-season annuals are frequently used during the summer forage slump when perennial pasture growth and quality are reduced. Research has shown that brown mid-rib sorghum × sudangrass (BMR SSG; Sorghum bicolor L. × S. arundinaceous Desv.) and pearl millet (PM; Pennisteum glaucum L.R. Br.) with crabgrass ( Digitaria sanguinalis (L.) Scop.) tended to have greater ADG (0.98 kg) than sorghum × sudangrass or peal millet alone (0.85 kg). However, non-BMR and BMR SSG tended to have greater gains per hectare than PM or PM + crabgrass (246, 226, 181, and 188 kg/ha, respectively). Feeding of brown mid-rib sorghum × sudangrass reduced daily production of CH4 and CH4 per gram of NDF fed by 66% and 50%, respectively, compared with a perennial cool-season forage in continuous culture. Cool- and warm-season annual pastures not only provide increased animal gains, but also increase soil cover and in vitro data suggest that annual forages (i.e., brassicas and warm-season annual grasses) decrease enteric CH4 emissions. Establishment method, grazing management, and weather conditions all play important roles in the productivity and environmental impact of these systems. A more complete life cycle analysis is needed to better characterize how management and climatic conditions impact the long-term economic and environmental sustainability of grazing annuals.